Surveys in combinatorics, 1995 - Rowlinson, Peter (Cambridge University Press, 1995)
The fifteenth British Combinatorial Conference took place in July 1995 at the University of Stirling. This volume consists of the papers presented by the invited lecturers at the meeting, and provides an up-to-date survey of current research activity in several areas of combinatorics and its applications. These include distance-regular graphs, combinatorial designs, coding theory, spectra of graphs, and randomness and computation. The articles give an overview of combinatorics that will be extremely useful to both mathematicians and computer scientists
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Combinatorial analysis / Congresses; Kombinatorik; Konferenzschrift